Digital Mental Health Interventions for Depression. Issue 1 (February 2022) - Himle, Joseph A.; Weaver, Addie; Zhang, Anao; Xiang, Xiaoling
Highlights: Digital mental health interventions are a promising way to disseminate evidence-supported therapy for depression. Research supports the efficacy of digital cognitive-behavioral interventions for depression. There is a need to make digital mental health interventions for depression more appealing. Entertaining forms of digitally-based CBT hold promise as a method to increase treatment engagement. Abstract: This paper provides an overview of the of digital mental health (DMHI) interventions for depression. The paper begins with a description of the clinical context and services needs for persons experiencing depressed mood. It is well-known that there is a large gap between the availability of evidence-supported psychotherapy for depression and the large number of people who would likely benefit from it. DHMIs based on a cognitive-behavioral (CBT) model have shown substantial promise as a method to deliver tested-effective treatment to large numbers of people experiencing depression. The article continues with a review of clinical research evaluating DMHIs for depression with a special emphasis on CBT. The article also reviews both the strengths and challenges associated with the clinical use of DHMI for depression. Next, the article continues with a description of a newly-developed DHMI for depression that uses an entertaining approach to deliver well-established CBT strategies. Finally, the paper concludes with a discussion of the need for further research and development of DHMIs for persons experiencing depression.